PENYULUHAN KESEHATAN PENTINGNYA PENGGUNAAN SEAT BELT PADA PEMOBIL UNTUK MENCEGAH TERJADINYA CEDERA TULANG BELAKANG - Mahadewa, T.G.B; Maliawan, S.; Golden, N.; Niryana, I.W.; Wardhana, D.P.W.; Awyono, S.; Putra, K.K. (Buletin Udayana Mengabdi; Vol 21 No 2 (2022): Buletin Udayana MengabdiDO - 10.24843/BUM.2022.v21.i02.p14, 2022)
The increased population is followed by an increase quantity of vehicles, therefore increased number of vehicles accidents could happen. Other than mortality rate, other issue that might occur was due to spinal cord injury. Spinal cord injury was not only causing health and medical problem, but socio-economic and psychology morbidity for the patients and family. The general concept of neurosurgery is to applied the principles of science with holistic approach and comprehensively. The comprehensive principle means that the sciences do not only emphasize the curative side, but also on the promotive, preventive and rehabilitative aspects. One of the promotive and preventive aspect that can be done is to provide education to the public about healthy lifestyles so that people can avoid a condition that might cause health morbidity. Bedah Saraf Bersama Masyarakat held by Neurosurgery Residency Programme FK UNUD/Sanglah Hospital is one of the community service activities. In an effort to prevent spinal cord injuries for drivers, the Neurosurgery Residency Programme, FK UNUD/Sanglah Hospital decided to held an interactive talkshow as public health promotion, for the importance of using seatbelts for drivers. The general purpose of this program is to provide information and education, especially in prevention of diseases in the field of neurosurgery to the community.   Keywords: Spine, spinal cord injury, public health promotion, seatbelt.